JWST Spectroscopy of (142) Polana: Connection to NEAs (101955) Bennu and (162173) Ryugu - Anicia Arredondo; Tracy M. Becker; Maggie M. McAdam; Andrew S. Rivkin; Stephanie Jarmak; Ian Wong (The Planetary Science Journal)
The new Polana collisional family is the hypothesized origin of the near-Earth asteroids (101955) Bennu, which was the target of the NASA OSIRIS-REx mission, and (162173) Ryugu, which was the target of the JAXA Hayabusa2 mission. We present JWST Near Infrared Spectrograph and Mid-Infrared Instrument spectroscopy of the parent body of the family, (142) Polana, and compare it with spacecraft and laboratory data of both near-Earth asteroids. We find that the near-infrared spectrum of Polana is similar to that of the returned sample from both Bennu and Ryugu but has a slope that differs from that of the global average spectra taken by both spacecraft. The mid-infrared Polana spectrum differs in shape from the global average spectrum of Bennu, possibly because of porosity, space weathering, or grain size. Spectral features at similar wavelengths in the spectra of Polana and those of Bennu and Ryugu support the hypothesis that both asteroids originated in the Polana family.